Pengaruh Mental Toughness dan Kecerdasan Emosi terhadap Kecemasan Olahraga pada Atlet Basket SMA Cita Hati Surabaya dalam Menghadapi Event DBL - Oktaviani, Nabila Rahmi; Prihastuti, Prihastuti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study was to determine the effect of mental toughness and emotional intelligence on exercise anxiety. This study uses a quantitative approach with an asymmetric regression research design. In this study, a sample of 24 basketball athletes from Cita Hati Surabaya High School was used with a sampling technique, namely purposive sampling. Data analysis used multiple regression analysis techniques anxiety. Multiple regression analysis revealed that F = 1.874 with a significance of 0.178 > 0.05 was not significant. Arinya, you stated that mental toughness and emotional intelligence have no effect on sports anxiety. While partially on the mental toughness variable, the value of t = -1.546 is obtained with a significance of 0.137 > 0.05, not significant. This means that the mental toughness variable partially has no significant effect on the sports anxiety variable. In the emotional intelligence variable, the value of t = -0.888 is obtained with a significance of 0.385 > 0.05, which is not significant. This means that the emotional intelligence variable partially has no significant effect on the sports anxiety variable.